Typology and distribution of small farms in Europe: towards a better picture. Land Use Policy - Guimoar, Nuno (2018)
The contribution of small farms to local food supply, food security and food sovereignty is widely acknowledged at a global level. In the particular case of Europe, they often are seen as an alternative to large and specialised farms. Assessing the real role of small farms has been limited by a lack of information, as small farms are frequently omitted from agricultural censuses and national statistics. It is also well acknowledged that small farms diﬀer widely, and are distributed according to diﬀerent spatial patterns across Europe, fulﬁlling diﬀerent roles according to the agriculture and territorial characteristics of each region. This paper presents the result of a novel classiﬁcation of small farms at NUTS-3 level in Europe, according to the relevance of small farms in the agricultural and territorial context of each region, and based on a typology of small farms considering diﬀerent dimensions of farm size. The maps presented result from an extensive data collection and variables selected according toEuropean wideexpert judgement, analysed with advanced cluster procedures.The results provide ﬁne grained picture of the role of small farms at the regional level in Europe today, and are expected to support further data analysis and targeted policy intervention